Pengaruh Kualitas Produk dan Layanan terhadap Kepuasan dan Loyalitas Pelanggan Merek Uniqlo - Sebayang, Sri Kasih; Didin Hikmah Perkasa (Lembaga Teewan Journal Solutions, 2026)
This study aims to examine the influence of product quality and service quality on customer satisfaction and their impact on customer loyalty toward the Uniqlo brand. The study is motivated by the increasingly competitive fashion industry, which requires companies not only to provide high-quality products but also to deliver superior services that enhance customer satisfaction and foster long-term loyalty. This research employed a quantitative explanatory approach. Data were collected through questionnaires distributed to 50 respondents using a consecutive sampling technique and analyzed using descriptive statistics and path analysis. The findings reveal that product quality has a positive and significant effect on customer satisfaction (β = 0.633; p < 0.001), while service quality also has a positive and significant effect (β = 0.331; p = 0.001). Simultaneously, both variables explain 82.1% of the variance in customer satisfaction (R² = 0.821). Furthermore, customer satisfaction has a positive and significant effect on customer loyalty (β = 0.815; p < 0.001), explaining 66.4% of the variance in customer loyalty (R² = 0.664). Customer satisfaction also mediates the relationship between product quality, service quality, and customer loyalty. The study concludes that strengthening customer loyalty requires companies to consistently maintain product and service quality in order to create customer satisfaction. Therefore, Uniqlo is recommended to strengthen product value communication, improve employees' product knowledge, and continuously enhance the overall shopping experience to sustain customer loyalty.